Special rare earth antibacterial master batch for PVC antibacterial air conditioner condensate pipe and preparation method of special rare earth antibacterial master batch

By using a combination of rare earth antibacterial agent and nanomaterial in PVC air conditioner condensate pipe, combined with environmentally friendly plasticizer and composite compatibilizer, the problem of poor antibacterial performance of PVC air conditioner condensate pipe is solved, and efficient and environmentally friendly antibacterial effect is achieved.

CN119684730AInactive Publication Date: 2025-03-25ZHEJIANG AKAN IND CO LTD

Patent Information

Application Number
CN202510205801.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing PVC air-conditioning condensate pipes have poor antibacterial properties, and the rare earth antibacterial agents have poor compatibility and dispersion with PVC resin.

Method used

The fine design of rare earth antibacterial agents and nanomaterials, combined with environmentally friendly plasticizers, composite compatibilizers and optimized preparation technology, PVC antibacterial masterbatches with excellent antibacterial performance and good stability were prepared.

Benefits of technology

It significantly improves antibacterial performance, the material is versatile and environmentally friendly and sustainable, solving the problem of insufficient antibacterial ability of traditional PVC materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a special rare earth antibacterial master batch for a PVC antibacterial air conditioner condensate pipe and a preparation method of the special rare earth antibacterial master batch. The problems that an existing PVC condensate pipe is poor in antibacterial performance, and a rare earth antibacterial agent and PVC resin are poor in compatibility and dispersity are solved. The master batch comprises PVC carrier resin, a rare earth antibacterial agent, a dispersing agent, a plasticizer, a heat stabilizer, a lubricant and a bulking agent, and the rare earth antibacterial agent is prepared by mixing rare earth oxide and inorganic oxide according to a specific proportion and carrying out mechanical dispersion, high-energy dispersion, secondary mechanical dispersion, drying, tunnel kiln firing and grinding treatment. The preparation method of the special rare-earth antibacterial master batch for the PVC antibacterial air conditioner condensate pipe comprises the steps of raw material pretreatment, raw material premixing, coupling treatment, mixing and plasticizing, melt extrusion, granulation molding and the like, and through a refining process and a supercritical carbon dioxide technology, it is ensured that a rare-earth antibacterial agent is uniformly dispersed and stably combined in a PVC matrix; the master batch with excellent antibacterial property, thermal stability and mechanical property is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a rare earth antibacterial masterbatch for a PVC antibacterial air-conditioning condensing water pipe and a preparation method thereof. Background Art

[0002] In modern buildings and industries, air conditioning systems are key equipment for maintaining a comfortable indoor environment, and air conditioning condensate pipes are responsible for timely discharging condensate generated during indoor heat exchange. However, condensate pipes are in a state of high humidity or even water accumulation for a long time, which is prone to breeding bacteria and mold. These microorganisms not only produce volatile substances with pungent odors such as hydrogen sulfide, but also corrode PVC pipes through metabolic products, causing corrosion, thinning, and even rupture, shortening the service life of the pipes, and increasing maintenance and replacement costs.

[0003] In the design and manufacturing process of traditional PVC condensate pipes, the main focus is on its basic physical and mechanical properties such as strength, toughness and chemical corrosion resistance, but the antibacterial needs are not fully considered. The material itself cannot effectively inhibit the growth of microorganisms. With the improvement of people's requirements for indoor environmental hygiene and the demand for long-term stable operation and reduced maintenance costs of building facilities, the development of condensate pipes with antibacterial properties has become particularly important. Rare earth antimicrobial agents have good antibacterial effects and stability due to their special electronic structure and chemical activity, but their application in the research and development of special masterbatches for PVC air-conditioning condensate pipes still faces many technical challenges and requires further exploration and research. Summary of the invention

[0004] The purpose of the present invention is to provide a rare earth antibacterial masterbatch specially used for PVC antibacterial air-conditioning condensation water pipes and a preparation method thereof, so as to solve the problems of poor antibacterial performance of existing PVC air-conditioning condensation water pipes, poor compatibility and dispersibility of rare earth antibacterial agents with PVC resins, and to prepare PVC antibacterial masterbatch with excellent antibacterial performance and good stability to meet the antibacterial requirements of air-conditioning condensation water pipes.

[0005] The present invention provides a rare earth antibacterial masterbatch specially used for PVC antibacterial air-conditioning condensing water pipes and a preparation method thereof. The invention adopts the fine design of rare earth antibacterial agents and nanomaterials, combines environmentally friendly plasticizers, composite compatibilizers and optimized preparation processes, realizes significant improvement of antibacterial performance, multifunctional expansion of materials and environmental sustainability of production, and provides an efficient and environmentally friendly solution for the antibacterial application of PVC air-conditioning condensing water pipes.

[0006] The present invention provides a rare earth antibacterial masterbatch for PVC antibacterial air conditioner condensation water pipe, which is composed of the following raw materials in parts by weight: 80-90 parts of PVC carrier resin, 10-20 parts of rare earth antibacterial agent, 0.5-2.0 parts of dispersant, 5-10 parts of plasticizer, 4-6 parts of heat stabilizer, 0.5-1.5 parts of lubricant, and 3-5 parts of compatibilizer. After a large number of experimental verifications, this raw material ratio can effectively reduce costs and improve production efficiency while ensuring excellent antibacterial properties. The rare earth antibacterial masterbatch specially used for PVC antibacterial air-conditioning condensing water pipes of the present invention is composed of a variety of raw materials such as PVC carrier resin and rare earth antibacterial agent in a specific proportion. The masterbatch formula of the present invention organically combines the rare earth antibacterial agent with a variety of functional additives to form an antibacterial masterbatch formula specifically for PVC air-conditioning condensing water pipes. By accurately proportioning rare earth antibacterial agents including zinc oxide and rare earth oxides with other key components such as nano-grade rare earth oxides, environmentally friendly plasticizers, and composite compatibilizers, not only excellent antibacterial performance is achieved, but also the processing performance, thermal stability and environmental protection of the material are taken into account. This formula design breaks through the limitations of traditional PVC antibacterial masterbatches, provides an efficient and sustainable solution to the problem of microbial growth in condensing water pipes, and expands the application potential of PVC materials in high humidity environments.

[0007] The combination of inorganic oxides and rare earth oxides in a specific ratio in the present invention achieves a synergistic antibacterial effect between the inorganic oxides and the rare earth oxides, significantly improves the antibacterial performance, and optimizes the cost. The addition of rare earth oxides not only enhances the thermal stability and chemical stability of the material, but also optimizes the microstructure, improves the density and mechanical properties of the material, and enables it to maintain a stable antibacterial effect in a complex environment, thereby better meeting the actual use requirements of air conditioning condensation water pipes.

[0008] Preferably, the rare earth antibacterial agent comprises an inorganic oxide and a rare earth oxide, and the mass fraction ratio of the inorganic oxide to the rare earth oxide is 18-33:8-14; the inorganic oxide comprises zinc oxide, manganese oxide, and titanium oxide, and the rare earth oxide comprises nano-lanthanum-cerium composite oxide, praseodymium oxide, and neodymium oxide. The composition of the rare earth antibacterial agent in the present invention realizes the synergistic effect of rare earth oxide and inorganic oxide. Traditional antibacterial agents are mainly single inorganic antibacterial agents such as zinc oxide and titanium oxide. The present invention combines rare earth oxide (nano-lanthanum-cerium composite oxide, praseodymium oxide, neodymium oxide) with inorganic oxide (zinc oxide, manganese oxide, titanium oxide) to form a new type of composite antibacterial system, which not only exerts the antibacterial advantages of each component, but also further enhances the antibacterial effect through synergistic effect. Inorganic oxides (zinc oxide, manganese oxide, titanium oxide) mainly exert antibacterial effects by releasing metal ions and destroying bacterial cell membranes. Rare earth oxides (especially nano-lanthanum-cerium composite oxides) have high specific surface area, strong adsorption capacity and special catalytic properties, which make rare earth oxides show excellent performance in antibacterial, especially at the nanoscale, which can fully contact with bacteria at the microscopic level, and its antibacterial activity is significantly higher than that of traditional inorganic antibacterial agents. Nano-lanthanum-cerium composite oxides can produce active oxygen under light conditions to destroy the cell structure of bacteria. This combination of multiple antibacterial mechanisms makes the antibacterial effect more comprehensive and lasting, and can effectively inhibit the growth of a variety of bacteria and molds.

[0009] The mass ratio of inorganic oxides to rare earth oxides is 18-33:8-14. This ratio is the best range obtained through a large number of experimental optimizations. It not only ensures the uniform dispersion of the antimicrobial agent in the PVC matrix, but also maximizes the synergistic antimicrobial effect of each component, achieving the best balance between antimicrobial performance and physical properties; by precisely controlling the ratio of inorganic oxides to rare earth oxides, while ensuring antimicrobial performance, the thermal stability, mechanical strength and other physical properties of the PVC masterbatch are optimized. Although rare earth oxides have excellent antimicrobial properties, they are relatively expensive. By reasonably adjusting the ratio of inorganic oxides to rare earth oxides, the production cost can be reduced while ensuring the antimicrobial effect.

[0010] The rare earth antibacterial masterbatch of the present invention is optimized specifically for the application scenario of the air conditioning condensation water pipe. The air conditioning condensation water pipe is easy to breed bacteria and mold during use, resulting in the generation of odor and dirt. By adding the rare earth antibacterial agent prepared above to the masterbatch of the present invention, the growth of bacteria can be effectively inhibited, the service life of the pipe can be extended, and the hygienic performance of the air conditioning system can be improved. During the preparation process, the present invention adopts advanced processes such as high-energy dispersion and secondary mechanical dispersion to ensure the uniform dispersion of the rare earth antibacterial agent in the PVC matrix, further improving the stability of the antibacterial performance and physical properties.

[0011] In the rare earth antibacterial agent of the present invention, rare earth oxides and inorganic oxides improve antibacterial properties through multiple synergistic mechanisms. When the kiln is baked at high temperature, the electrons of zinc oxide are excited to the 4f electron orbit of the rare earth element. This electron transfer changes the electron cloud distribution of the system, enhances the antibacterial function of zinc ions, and zinc ions interact with biological molecules in bacterial cells, destroying bacterial cell membranes and interfering with metabolic processes, thereby inhibiting or killing bacteria. At the same time, electron transfer also changes the electronic structure of rare earth oxides, and the electrons in rare earth oxides are excited to a higher energy level, further enhancing their antibacterial properties and making them more likely to interact with bacteria.

[0012] The synergistic effect between inorganic oxides and rare earth oxides forms a stronger antibacterial property through electron transfer. Zinc oxide, titanium oxide and other inorganic oxides have certain photocatalytic activity. The addition of rare earth oxides can reduce the band gap of inorganic oxides, so that the material can absorb more visible light and increase the probability of generating photogenerated carriers (electron-hole pairs). On the other hand, rare earth ions act as capture centers for electrons or holes, inhibiting the recombination of photogenerated carriers and extending their lifespan. Photogenerated carriers react with oxygen and water in the air to produce hydroxyl radicals, superoxide anions and other active oxygen species with strong oxidizing properties, oxidizing organic matter in bacteria, destroying the structure and function of bacteria, and achieving the antibacterial purpose.

[0013] Furthermore, the mass ratio of rare earth to inorganic oxide in the inorganic oxide and rare earth oxide is 3:7, the mass ratio of zinc oxide, manganese oxide and titanium oxide is 3-4:2-5:1-5, and the mass ratio of nano-lanthanum-cerium composite oxide, praseodymium oxide and neodymium oxide is 5-7:2-4:1-3; the particle size range of the nano-lanthanum-cerium composite oxide is 20-80 nanometers, and the molar ratio of lanthanum to cerium is 1:1-5. Cerium oxide has a unique electronic structure and redox properties, which can not only enhance the photocatalytic activity of zinc oxide, but also play a stabilizing and synergistic role in the antibacterial process, thereby improving the durability of the antibacterial system. Praseodymium oxide further optimizes the semiconductor properties of zinc oxide, cooperates with cerium oxide, promotes the separation and migration of photogenerated carriers under different illumination conditions, and enhances the antibacterial effect. Lanthanum oxide has a large ionic radius, which can improve the dispersibility of the antibacterial agent in PVC resin, enhance the binding force with the carrier, and at the same time has a certain destructive effect on the cell wall and cell membrane of bacteria, thereby assisting in antibacterial. Neodymium oxide can adjust the crystal structure of the antibacterial agent, enhance the stability of photogenerated carriers in the photocatalytic process, reduce the probability of recombination, prolong the photocatalytic antibacterial time of the antibacterial agent, and inhibit bacterial growth by interacting with certain biological molecules of bacteria in the antibacterial process. By rationally proportioning the four rare earth oxides, the rare earth antibacterial agent of the present invention realizes multi-dimensional synergistic antibacterial, and the electronic structure and chemical property differences of different rare earth elements make it play different roles in the antibacterial process, such as cerium oxide and praseodymium oxide enhance photocatalytic activity, lanthanum oxide improves dispersibility and auxiliary antibacterial, neodymium oxide regulates crystal structure and inhibits bacterial growth, and jointly builds a more powerful and lasting antibacterial system, which is difficult to achieve with a single or simple binary rare earth antibacterial agent. Lanthanum oxide is introduced into the formula to improve dispersibility, so that the antibacterial agent is evenly distributed in the PVC resin, the agglomeration phenomenon is reduced, the stability and processing performance of the antibacterial masterbatch are improved, and the antibacterial agent can effectively play a role in the production process of PVC antibacterial air conditioning condenser water pipe, while not affecting the physical properties of the pipe material, and optimizing the compatibility with the PVC carrier. At the same time, the small-particle nano-lanthanum-cerium composite oxide has a large specific surface area, which can increase the contact area with bacteria and improve the antibacterial activity. The specific molar ratio of lanthanum to cerium can synergistically enhance the antibacterial and catalytic properties, and better play the antibacterial role at the molecular level.

[0014] The present invention further defines that the mass ratio of rare earth to inorganic oxide in the inorganic oxide and rare earth oxide is 3:7, and the mass ratio of zinc oxide, manganese oxide and titanium oxide is 3-4:2-5:1-5. By optimizing the ratio of rare earth to inorganic oxide and the ratio of each component inside the inorganic oxide, the best balance between antibacterial property and physical property is achieved, and the multiple antibacterial mechanisms of inorganic oxide and rare earth oxide are combined, the antibacterial effect and stability are significantly enhanced, and the balance between economy and performance is achieved.

[0015] Preferably, the dispersant is a titanate coupling agent, the plasticizer is an environmentally friendly plasticizer tributyl citrate, the heat stabilizer is a calcium zinc composite heat stabilizer, and the lubricant is polyethylene wax. The selection of these environmentally friendly raw materials reduces pollution to the environment and harm to human health, and meets the requirements of green development.

[0016] The present invention uses a titanate coupling agent as a dispersant in the rare earth antibacterial masterbatch specially used for PVC antibacterial air conditioner condensation water pipes, improves interface bonding, and enhances dispersion effect and processing performance. It is a special design for antibacterial masterbatch that is different from traditional dispersants.

[0017] PVC carrier resin and inorganic components such as rare earth antimicrobial agents have great differences in chemical properties. When directly mixed, the compatibility between the two is poor, and phase separation and agglomeration are prone to occur. Titanate coupling agents have a unique molecular structure. One end of the molecule can react chemically with the hydroxyl group on the surface of the rare earth antimicrobial agent (zinc oxide, rare earth oxide, etc.) to form a chemical bond; the other end can entangle or react chemically with the PVC resin molecular chain, thereby forming a good interface bond between the inorganic antimicrobial agent and the organic PVC resin, enhancing the compatibility between the two, and allowing the antimicrobial agent to be evenly dispersed in the PVC matrix. Secondly, the titanate coupling agent can reduce the surface energy of the inorganic antimicrobial agent particles and reduce the agglomeration force between the particles. By forming a coating layer on the surface of the antimicrobial agent particles, it prevents the particles from re-aggregating, thereby improving the uniformity of the antimicrobial agent in PVC, which helps to give full play to the antimicrobial properties of the rare earth antimicrobial agent. At the same time, it can also avoid local performance differences caused by the agglomeration of the antimicrobial agent, and ensure the stability of the overall performance of the antimicrobial masterbatch. Good dispersion effect can improve the fluidity and processing performance of materials. During the PVC processing, the evenly dispersed antibacterial agent will not hinder the movement of the PVC molecular chain, making the material easier to plasticize and shape. Using titanate coupling agent as a dispersant can reduce energy consumption and equipment wear during processing, and improve production efficiency and product quality. Dispersants commonly used in traditional PVC processing, such as stearic acid and its salts, mainly reduce the friction and surface energy between materials through physical action to achieve dispersion effect, while titanate coupling agent improves interface bonding through chemical reaction. This mechanism of action is more in-depth and effective, which can not only improve dispersibility, but also enhance the mechanical properties and other properties of the material. Compared with traditional dispersants, it has unique advantages. In the application scenario of rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condensate pipes, according to the characteristics of rare earth antibacterial agents and PVC carrier resins, titanate coupling agent is selected as a dispersant, which brings better antibacterial performance, processing performance and product stability to the production and use of PVC antibacterial air-conditioning condensate pipes, and provides new ideas and methods for the development of technology in this field.

[0018] The present invention uses tributyl citrate as an environmentally friendly plasticizer in the rare earth antibacterial masterbatch for PVC antibacterial air conditioner condensing water pipe. Compared with traditional phthalate plasticizers, tributyl citrate has good biodegradability, and will not release harmful substances into the environment during use, has no toxic effects on the human body, will not cause health problems such as endocrine disruption, and meets environmental regulations. At the same time, tributyl citrate is well compatible with a variety of high molecular materials such as PVC, can be evenly dispersed in a polymer matrix, effectively reduces the force between polymer molecular chains, increases the flexibility and fluidity of molecular chains, thereby giving the material good processing properties and use performance. It has good light resistance, heat resistance and water resistance, can ensure the stability of the material under different environmental conditions, in high temperature, humidity or light and other environments, is not easy to volatilize, migrate or seep out, can make the product keep softness and physical properties for a long time, extend the service life of the product, can while ensuring environmental performance, give the condensing water pipe good flexibility and processing performance.

[0019] The present invention uses a calcium-zinc composite heat stabilizer as an environmentally friendly heat stabilizer in a rare earth antibacterial masterbatch specially used for PVC antibacterial air-conditioning condensing water pipes. The masterbatch takes calcium salt and zinc salt as main components and is supplemented with other additives. The masterbatch has good thermal stability and processing performance, can meet the production requirements of PVC antibacterial air-conditioning condensing water pipes, and complies with environmental protection standards. The masterbatch is a substitute for lead salt heat stabilizers.

[0020] The present invention uses polyethylene wax as a lubricant in the rare earth antibacterial masterbatch specially used for PVC antibacterial air conditioner condensing water pipes. The polyethylene wax has a low melting point, high hardness and good chemical stability, and can reduce the friction between materials and equipment during the PVC processing process. At the same time, it can also reduce the melt viscosity of the PVC resin, improve the fluidity of the material, make the rare earth antibacterial agent and the like evenly distributed in the PVC matrix, and improve the quality and performance of the antibacterial masterbatch.

[0021] Preferably, the compatibilizer is a composite of maleic anhydride grafted PVC compatibilizer and dioctyl terephthalate or epoxidized soybean oil, and the mass ratio of the maleic anhydride grafted PVC compatibilizer to dioctyl terephthalate or epoxidized soybean oil is 4-6:2-4. This composite compatibilizer can effectively improve the compatibility between the components and improve the comprehensive performance of the masterbatch.

[0022] The present invention uses a composite of maleic anhydride grafted PVC compatibilizer and dioctyl terephthalate or epoxidized soybean oil as a compatibilizer in a rare earth antibacterial masterbatch specially used for PVC antibacterial air conditioner condensation water pipes, and its function is to improve the compatibility between the PVC carrier resin and the rare earth antibacterial agent (inorganic component). The maleic anhydride group in the maleic anhydride grafted PVC can interact with the polar group on the surface of the rare earth antibacterial agent, while the PVC segment has good compatibility with the matrix PVC, thereby playing a bridging role and enhancing the binding force between the two. Dioctyl terephthalate or epoxidized soybean oil can not only be used as a plasticizer to improve the flexibility and processing performance of the material, but also to a certain extent assist the compatibility of the maleic anhydride grafted PVC reinforcement system, so that the rare earth antibacterial agent can be evenly dispersed in the PVC matrix, and the performance and quality of the antibacterial masterbatch are improved. Dioctyl terephthalate has good migration resistance and can exist more stably in plastic products, reducing the possibility of plasticizer migration to the surrounding environment. In the long-term use of PVC pipes using dioctyl terephthalate as a plasticizer, the plasticizer is not easy to leak out and pollute the environment or contact other substances, reducing the potential threat to the environment and human health. Epoxidized soybean oil is made from soybean oil through epoxidation reaction. Soybean oil is a renewable natural resource with a wide range of sources and sustainability. Compared with petroleum-based plasticizers, the use of epoxidized soybean oil can reduce dependence on limited petroleum resources and conform to the concept of sustainable development. At the same time, epoxidized soybean oil has good biodegradability and can be decomposed into harmless substances such as carbon dioxide and water by microorganisms in the natural environment. It will not persist in the environment like some traditional plasticizers, and has less impact on the ecological environment such as soil and water. Epoxidized soybean oil is non-toxic, odorless, harmless to human health, and has certain thermal stability and weather resistance. At present, the common compatibilization system is relatively simple, and most of them use a single compatibilizer to improve the compatibility between polymers and additives. The maleic anhydride grafted PVC compatibilizer and dioctyl terephthalate or epoxidized soybean oil are used as a compatibilizer to form a composite compatibilization system. This composite system combines the dual functions of compatibilization and plasticization, and improves the material performance through the synergistic effect between different components. In the specific application scenario of rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condensation water pipes, this composite compatibilization system is designed for the special needs of the material. The compatibilizer made of this composite takes into account the characteristics of rare earth antibacterial agents and PVC resins, as well as the requirements of condensation water pipes for material performance during actual use, such as antibacterial properties, flexibility, stability, etc., and optimizes these properties through a unique combination of ingredients. Different from the traditional general-purpose compatibilization solution, it has strong pertinence and innovation.

[0023] The method for preparing rare earth antibacterial masterbatch specially used for PVC antibacterial air-conditioning condensing water pipes of the present invention realizes efficient dispersion and stable combination of rare earth antibacterial agents in a PVC matrix through refined raw material pretreatment, negative pressure premixing, segmented temperature rising coupling treatment, supercritical carbon dioxide assisted plasticization and other steps, which not only effectively avoids oxidation and agglomeration of the antibacterial agent, but also gives the material excellent antibacterial performance, thermal stability and multifunctional characteristics by optimizing process parameters, while embodying the concepts of environmental protection and sustainable development, and significantly improving the overall performance and application value of PVC antibacterial masterbatch.

[0024] The present invention provides a method for preparing a rare earth antibacterial masterbatch specially used for PVC antibacterial air-conditioning condensing water pipe, which specifically comprises the following steps: S1 Raw material pretreatment: weigh an inorganic oxide mixture of zinc oxide, manganese oxide, and titanium oxide in a mass ratio of 3-4:2-5:1-5, weigh a rare earth oxide mixture of nano lanthanum-cerium composite oxide, praseodymium oxide, and neodymium oxide in a mass ratio of 5-7:2-4:1-3, so that the mass ratio of rare earth to inorganic oxide in the inorganic oxide and rare earth oxide is 3:7, adopt a doping process, and prepare a rare earth antibacterial agent through mixing, mechanical dispersion, high-energy dispersion, secondary mechanical dispersion, drying, tunnel kiln firing, and grinding; weigh 4-6 parts of maleic anhydride grafted PVC compatibilizer and 2-4 parts of dioctyl terephthalate or epoxidized soybean oil, and add the weighed two raw materials into a high-speed mixer. or in a blender, mixing and preparing a composite of a maleic anhydride grafted PVC compatibilizer and dioctyl terephthalate or epoxidized soybean oil to obtain a compatibilizer; accurately weighing 80-90 parts by weight of a dried PVC carrier resin, 0.5-2.0 parts of a titanate coupling agent, 5-10 parts of tributyl citrate, 4-6 parts of a calcium-zinc composite heat stabilizer, 0.5-1.5 parts of a polyethylene wax, 3-5 parts of the compatibilizer prepared above, and 10-20 parts of the rare earth antibacterial agent prepared above, respectively, and setting aside; preparing a rare earth antibacterial agent and a composite compatibilizer through a doping process and baking in a high-temperature kiln, thereby laying a foundation for uniform dispersion in subsequent processes and ensuring the compatibility and synergy of each component in a PVC matrix.

[0025] S2 raw material premixing: add the weighed dry PVC carrier resin and part of the titanate coupling agent into a mixing device with heating and vacuuming functions, fully mix the dispersant and PVC resin at a low temperature of 60-80°C and a stirring speed of 300-600r / min for 15-25 minutes, then gradually increase the temperature to 100-120°C, turn on the vacuuming device at the same time, control the pressure in the system at -0.08 to -0.06MPa, slowly add the rare earth antibacterial agent obtained by pretreatment, continue stirring for 20-30 minutes during the addition process, and keep the stirring speed at 400-700r / min. Accurate pressure control is achieved through advanced pressure sensors and automatic control systems, and negative pressure is used to remove air and moisture in the system to avoid oxidation and agglomeration of the antibacterial agent, thereby improving the stability and dispersibility of the antibacterial agent and achieving refined operation.

[0026] S3 coupling treatment: the material treated as above is transferred to the reactor, and the stepwise heating method is adopted. It is first moistened at 80-100°C for 10-15 minutes, and then the temperature is raised to 110-130°C, and the remaining titanate coupling agent is slowly added. Under the condition of stirring speed of 600-1000r / min, the reaction is carried out for 20-30 minutes; the stepwise heating method combined with the control of specific temperature and stirring speed enhances the chemical bonding between the titanate coupling agent and the PVC matrix and the antibacterial agent, improves the efficiency and quality of the coupling reaction, and further improves the comprehensive performance of the material.

[0027] S4 Mixing and plasticizing: The coupled material is added into the hopper of a twin-screw extruder together with tributyl citrate, calcium-zinc composite heat stabilizer, polyethylene wax and a compatibilizer prepared by mixing in proportion, and supercritical carbon dioxide is injected at the same time to make additives such as rare earth antibacterial agents evenly dispersed in the PVC matrix; injecting supercritical carbon dioxide during the mixing and plasticizing stage not only reduces the melt viscosity and improves the dispersibility of the antibacterial agent, but also forms a microporous structure, giving the material additional multifunctional properties such as sound insulation and heat insulation.

[0028] S5 melt extrusion: adopts high shear mixing section, sets vacuum exhaust port in the middle of extruder, accurately controls vacuum degree at 0.08-0.09MPa, removes volatile water and coupling agent by-products, controls die pressure at 10-15MPa, and extrudes materials into strips through die head; through high shear mixing and precise vacuum degree and die pressure control, effectively removes volatile impurities and ensures uniformity and stability of materials.

[0029] S6 granulation molding: water-cooled strand pelletizing is adopted, and the extruded strips are cooled through a water trough, and the water temperature is controlled at 20-30℃, so that the material is quickly cooled and solidified within 1-3 minutes; the cooled material is pelletized by a pelletizer, and the speed of the pelletizer is controlled at 200-300r / min. The diameter after cutting is 2-3mm, and it is dried in an oven at 50-65℃ for 3-5 hours. The water-cooled strand pelletizing technology is adopted to quickly cool and solidify the material to ensure the molding quality of the particles; at the same time, unqualified particles and scraps are collected, crushed and screened, and then re-added to the raw materials for recycling at a mass ratio of 5-10%, which not only reduces waste, but also reduces production costs, reflecting the concept of environmental protection and sustainable development; finally, through multi-step refined control and parameter optimization, the efficient combination of rare earth antibacterial agent and PVC matrix is ​​achieved, and the synergistic effect of each component is fully exerted, so as to prepare a rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condenser water pipe with excellent antibacterial properties, thermal stability and mechanical properties.

[0030] In the preparation method of the rare earth antibacterial masterbatch specially used for PVC antibacterial air-conditioning condenser water pipes of the present invention, the raw material pretreatment step realizes efficient mixing and synergistic effect of the components through refined rare earth antibacterial agent preparation, design and preparation of composite bulking agent, and strict raw material drying and weighing, thereby significantly improving the performance of PVC antibacterial masterbatch.

[0031] Preferably, in the method for preparing the rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condenser water pipe of the present invention, the raw material pretreatment in step S1 specifically includes the following operations: S11 Preparation of rare earth antibacterial agent: A rare earth oxide mixture including nano lanthanum-cerium composite oxide, praseodymium oxide and neodymium oxide is mixed with an inorganic oxide mixture including zinc oxide, manganese oxide and titanium oxide in a mass ratio of rare earth to inorganic oxide of 3:7, and the rare earth antibacterial agent is obtained through mechanical dispersion, high-energy dispersion, secondary mechanical dispersion, drying, tunnel kiln firing and grinding. The synergistic effect of multiple antibacterial mechanisms is achieved by doping rare earth oxides (nano lanthanum-cerium composite oxide, praseodymium oxide, neodymium oxide) with inorganic oxides (zinc oxide, manganese oxide, titanium oxide). The uniform mixing of various components at the microscopic level and the stability and activity of the antibacterial agent are ensured through mixing, mechanical dispersion, high-energy dispersion, secondary mechanical dispersion, drying, tunnel kiln firing and grinding. Advanced processes such as high-energy dispersion and tunnel kiln firing are adopted, and the uniformity and stability of the antibacterial agent are ensured after high-temperature kiln baking, so as to give full play to the synergistic antibacterial effect of the rare earth antibacterial agent and significantly improve the antibacterial performance.

[0032] Preparation of S12 compatibilizer: accurately weigh 4-6 parts by mass of maleic anhydride grafted PVC compatibilizer and 2-4 parts of dioctyl terephthalate or epoxy soybean oil, add the weighed two raw materials into a high-speed mixer or a stirrer for mixing, the mixing speed is 500-1500r / min, the mixing time is 10-30 minutes, and a fully mixed and uniform composite of maleic anhydride grafted PVC compatibilizer and dioctyl terephthalate or epoxy soybean oil is obtained, which is the compatibilizer; the composite compatibilizer of maleic anhydride grafted PVC compatibilizer and dioctyl terephthalate or epoxy soybean oil is used, and a specific mixing process (precise control of mixing speed and time) is used to achieve efficient preparation of the compatibilizer, significantly improve the compatibility between the rare earth antibacterial agent and the PVC carrier resin, and improve the overall performance of the material.

[0033] S13 Preparation of other raw materials: Dry the PVC carrier resin at 80-100°C for 2-4 hours to remove moisture, ensuring the stability and uniformity of the material during subsequent processing; accurately weigh 80-90 parts by weight of the dried PVC carrier resin, 0.5-2.0 parts of titanate coupling agent, 5-10 parts of tributyl citrate, 4-6 parts of calcium zinc composite heat stabilizer, 0.5-1.5 parts of polyethylene wax, 3-5 parts of the above-prepared compatibilizer and 10-20 parts of the above-prepared rare earth antibacterial agent, and set them aside, ensuring the accuracy and repeatability of the formula and providing a guarantee for the production of high-quality products.

[0034] The raw material pretreatment step of the present invention forms a complete pretreatment process by organically combining the preparation of the rare earth antibacterial agent, the preparation of the compatibilizer, and the drying and weighing of the raw materials, which not only improves the production efficiency, but also ensures the uniform dispersion and stable combination of each component in the subsequent processing, and lays a solid foundation for the preparation of high-performance PVC antibacterial masterbatch.

[0035] Preferably, in the preparation method of the rare earth antibacterial masterbatch for PVC antibacterial air conditioner condenser water pipe of the present invention, the preparation of the rare earth antibacterial agent includes the following specific operations: an inorganic oxide mixture including 3-4 parts by mass of zinc oxide, 2-5 parts by mass of manganese oxide, and 1-5 parts by mass of titanium oxide is mixed with a rare earth oxide mixture including 5-7 parts by mass of nano lanthanum-cerium composite oxide, 2-4 parts by mass of praseodymium oxide, and 1-3 parts by mass of neodymium oxide according to the mass ratio of rare earth to inorganic oxide being 3:7; the rare earth is mixed with the inorganic oxide mixture including 3-4 parts by mass of zinc oxide, 2-5 parts by mass of manganese oxide, and 1-5 parts by mass of titanium oxide; the rare earth is mixed with the inorganic oxide mixture including 5-7 parts by mass of nano lanthanum-cerium composite oxide, 2-4 parts by mass of praseodymium oxide, and 1-3 parts by mass of neodymium oxide; the rare earth is mixed with the inorganic oxide mixture including 3-4 parts by mass of manganese oxide, and 1-5 parts by mass of titanium oxide; the rare earth is mixed with the inorganic oxide mixture including 5-7 parts by mass of nano lanthanum-cerium composite oxide, 2-4 parts by mass of praseodymium oxide, and 1-3 parts by mass of neodymium oxide; the rare earth is mixed with the inorganic oxide mixture including 5-7 parts by mass of ... The nano-lanthanum-cerium composite oxide, praseodymium oxide and neodymium oxide are added in the form of an ethanol solution after being ultrasonically treated at 100-300W for 30-60 minutes, and the ultrasonic treatment further refines the particles, improves the dispersibility, and enhances the uniformity of the antibacterial agent; the inorganic oxide is added in the form of a powder; the mixed roasted material is put into a dispersing device for mechanical dispersion for 20-30 minutes to mix the components evenly to form a paste mixture; the paste mixture is subjected to high-energy dispersion for 40-50 minutes to further refine the particles and ensure that the components are fully dispersed at the microscopic level. The mixture is then mechanically dispersed for 20-30 minutes to restore the uniformity of the mixture. The paste mixture is then dried at 115-125°C for 24-48 hours. After being thoroughly dried, it is fired in a tunnel kiln. The lumps are placed in a crucible and the firing temperature and time are controlled by a fully automatic intelligent arrangement device to ensure the accuracy and consistency of the firing process. The temperature of the firing buffer zone is raised from room temperature to 1400-1600°C, and the temperature of the high-temperature firing zone is maintained at 1400-1 The calcination time at 600°C is 2-4 hours, and the time in the cooling zone is 1-3 hours. Accurate temperature control can ensure the stability and activity of the antibacterial agent and improve the quality of the product. The high-temperature blended doped oxides that have been calcined are ground, first crushed and initially ground, and then finely ground to reach a particle size range of 200nm-150000nm. The particle size control ensures the uniform dispersion of the antibacterial agent in the PVC matrix, further improves the antibacterial performance and the stability of physical properties, and obtains the high-efficiency rare earth antibacterial agent of the present invention.

[0036] Mixing, mechanical dispersion, high-energy dispersion, secondary mechanical dispersion, and multi-step dispersion treatment ensure that the components are evenly mixed at the microscopic level. The traditional preparation process usually only includes simple mixing and mechanical dispersion, while the present invention further refines the particles through high-energy dispersion and secondary mechanical dispersion to ensure that the components are fully mixed and evenly mixed at the microscopic level, which not only improves the uniformity of the antibacterial agent, but also enhances its antibacterial properties; the drying and tunnel kiln firing steps ensure the stability and activity of the antibacterial agent. Under high temperature conditions, electrons obtain sufficient energy to achieve transfer and enhance the antibacterial properties of the product; the firing process removes impurities and enhances the chemical bonding between the components, thereby improving the stability and antibacterial properties of the antibacterial agent; the grinding process further optimizes the particle size distribution of the antibacterial agent, making it more suitable for dispersion in the PVC matrix.

[0037] In the preparation method of the rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condenser water pipes of the present invention, the mixing and plasticizing step realizes the uniform dispersion of the rare earth antibacterial agent in the PVC matrix and the significant improvement of material properties through precise material addition and temperature control, as well as the innovative application of supercritical carbon dioxide.

[0038] Preferably, in the method for preparing the rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condensing water pipe of the present invention, the step S4 of mixing and plasticizing specifically includes the following operations: S41 Material addition: The coupled material, tributyl citrate, calcium zinc composite heat stabilizer, polyethylene wax and a compatibilizer prepared by mixing in proportion are added into the hopper of the twin-screw extruder within 5-10 minutes, and the feeding speed is controlled at 5-10kg / h; by precisely controlling the material addition time and feeding speed, the uniform mixing and reaction of the components in the extruder are ensured to avoid accumulation and blockage.

[0039] S42 temperature setting: The temperature of zone 1 of the twin-screw extruder is 150-160℃, the temperature of zone 2 is 165-175℃, the temperature of zone 3 is 175-185℃, the temperature of zone 4 is 180-190℃, the temperature of the die head is 185-195℃, and the screw speed is controlled at 150-250r / min; the temperature and screw speed of the twin-screw extruder are set in sections so that the material can be properly processed in different areas to ensure the mixing and plasticizing effect and efficiency.

[0040] S43 supercritical carbon dioxide injection: Inject supercritical carbon dioxide with a pressure of 8-12MPa at 1-3% of the material mass, continue to inject and react for 10-20 minutes, so that additives such as rare earth antibacterial agents are evenly dispersed in the PVC matrix, reduce the melt viscosity and form a microporous structure; supercritical carbon dioxide has unique physical properties. During the injection process, it can not only reduce the melt viscosity, so that additives such as rare earth antibacterial agents are more evenly dispersed in the PVC matrix, but also disentangle the molecular chains and promote the reaction activity of the additives; at the same time, the microporous structure formed during the extrusion process gives the product good sound insulation, heat insulation and cushioning properties.

[0041] The mixed plasticizing step of the present invention organically combines operations such as material addition, temperature control and supercritical carbon dioxide injection to form a synergistically optimized mixed plasticizing process, which not only improves the comprehensive performance of the material, but also ensures the stability and repeatability of the production process by precisely controlling various parameters, thereby providing a guarantee for the preparation of high-quality products.

[0042] In summary, the present invention has the following beneficial effects: 1. The rare earth antibacterial masterbatch for PVC antibacterial air conditioner condensing water pipe of the present invention combines rare earth antibacterial agent with nanomaterial through raw material selection and proportioning, which not only ensures the synergistic effect between the components, but also effectively controls the cost while greatly improving the comprehensive performance of the product, solving the problem of insufficient antibacterial ability of traditional PVC materials; 2. The rare earth antibacterial agent used in the masterbatch of the present invention includes zinc oxide and rare earth oxide in a specific ratio. By combining rare earth oxide (nano lanthanum-cerium composite oxide, praseodymium oxide, neodymium oxide) with inorganic oxide (zinc oxide, manganese oxide, titanium oxide), the synergistic effect of multiple antibacterial mechanisms such as photocatalysis, ion release and catalytic decomposition is achieved, and multi-dimensional synergistic antibacterial is carried out. Different from the single antibacterial mechanism of traditional antibacterial agents, the antibacterial performance is significantly improved. The unique electronic structure and chemical properties of rare earth elements give the antibacterial agent efficient and lasting antibacterial ability, and its multi-pathway antibacterial mechanism effectively inhibits the growth of various bacteria and molds; through multi-step fine processing and high-temperature firing such as mixing, mechanical dispersion, high-energy dispersion, secondary mechanical dispersion, etc., the uniform dispersion and stability of the rare earth antibacterial agent in the PVC matrix are ensured; the particle size distribution of the antibacterial agent is optimized by high-temperature firing and fine grinding, so that the antibacterial agent maintains a good antibacterial effect under different environmental conditions such as light, humidity, temperature, etc., and the environmental adaptability of the PVC masterbatch is enhanced; 3. The rare earth antibacterial agent used in the masterbatch of the present invention includes nano lanthanum-cerium composite oxide, the particle size of which is controlled at 20-80 nanometers, has a larger specific surface area and higher activity, increases the contact area with bacteria, and improves the antibacterial activity. The specific molar ratio of lanthanum to cerium can synergistically enhance the antibacterial and catalytic properties, and better exert the antibacterial effect at the molecular level. The use of nano lanthanum-cerium composite oxide, combined with ultrasonic treatment, further refines the particles, improves the dispersibility, and enhances the activity and uniformity of the antibacterial agent. Different from conventional antibacterial agents, the addition of nano materials improves the dispersibility and stability of the antibacterial agent, thereby further improving the antibacterial performance and overall quality of the product; 4. Different from the disadvantage of poor stability of traditional PVC materials, the present invention adopts specific raw materials and processes to enhance the stability of materials, and the selected calcium-zinc composite heat stabilizer and reasonable formula system effectively inhibit the thermal decomposition of PVC resin during processing and use, significantly improving the thermal stability and mechanical properties of PVC materials, making them more suitable for use in high humidity environments, and solving the problem of easy aging of traditional PVC materials in humid environments; 5. The environmentally friendly plasticizer and heat stabilizer used in the rare earth antibacterial masterbatch formula for PVC antibacterial air conditioner condensing water pipe of the present invention are different from the phthalate plasticizers and lead salt heat stabilizers commonly used in traditional PVC materials, avoiding the harm of harmful substances contained in traditional materials to the environment and human health. At the same time, unqualified particles and scraps in the production process are recycled, realizing the effective circulation of resources, reducing the generation of waste, and complying with the concept of green production; 6. The present invention adopts a composite compatibilizer of maleic anhydride grafted PVC compatibilizer and dioctyl terephthalate or epoxidized soybean oil, which effectively improves the compatibility between the rare earth antibacterial agent and the PVC carrier resin, and improves the overall performance of the material. Different from the application of a traditional single compatibilizer, the compatibilizer prepared in the present invention adopts a composite design, which can effectively improve the compatibility between different components, and by enhancing the interface bonding force between the raw materials, the entire system is made more uniform and stable, thereby improving the comprehensive performance of the product, ensuring that the product has excellent performance in mechanical properties, thermal properties, etc.; 7. The preparation process of the rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condenser water pipe of the present invention is optimized through supercritical carbon dioxide technology, negative pressure premixing and staged heating. Supercritical technology can improve the microstructure of the material, and the negative pressure environment is conducive to removing impurities and volatiles. The staged heating can better control the reaction process, so that the various properties of the product reach the optimal state, improve the mixing uniformity of the raw materials, promote the chemical reaction, and ensure the uniform dispersion and stable combination of the rare earth antibacterial agent in the PVC matrix, thereby improving the quality and performance of the product. DETAILED DESCRIPTION

[0043] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

[0044] Example 1

[0045] S1. Raw material pretreatment: an inorganic oxide mixture including 3 parts by mass of zinc oxide, 2 parts by mass of manganese oxide, and 1 part by mass of titanium oxide is mixed with a rare earth oxide mixture including 6 parts by mass of nano-lanthanum-cerium composite oxide, 6 parts by mass of praseodymium oxide, and 2 parts by mass of neodymium oxide, in a ratio of rare earth to inorganic oxide of 3:7, the rare earth is added in the form of an ethanol solution of nano-lanthanum-cerium composite oxide, praseodymium oxide, and neodymium oxide after 200W ultrasonic treatment for 45 minutes, and the inorganic oxide is added in the form of powder; the mixed calcined material is The mixture is put into a dispersing device for mechanical dispersion for 25 minutes to mix the components evenly to form a paste mixture; the paste mixture is subjected to high-energy dispersion for 45 minutes to further refine the particles and ensure that the components are fully mixed and evenly mixed at the microscopic level to form a suspension with solid-liquid separation; the suspension is subjected to secondary mechanical dispersion for 25 minutes to restore the uniformity of the mixture, and then the paste mixture is dried at 120°C for 36 hours. After being thoroughly dried, it is fired in a tunnel kiln, and the lumps are placed in a crucible, and the roasting temperature is controlled by a fully automatic intelligent arrangement device. The temperature of the calcination buffer zone is raised from room temperature to 1500°C, the temperature of the high temperature calcination zone is maintained at 1500°C for 3 hours, and the temperature of the cooling zone is 2 hours; the high temperature mixed doped oxides after calcination are ground, first crushed and initially ground, and then finely ground to obtain a rare earth antibacterial agent; 5 parts by weight of maleic anhydride grafted PVC compatibilizer and 3 parts of dioctyl terephthalate or epoxidized soybean oil are weighed, and the two weighed raw materials are added into a high-speed mixer or a blender to mix and prepare maleic anhydride grafted PVC compatibilizer. A composite of a PVC compatibilizer and dioctyl terephthalate or epoxidized soybean oil is mixed at a speed of 1000 r / min for 20 minutes to obtain a compatibilizer; the PVC carrier resin is dried at 90° C. for 3 hours to remove moisture, and 85 parts of the dried PVC carrier resin, 1 part of a titanate coupling agent, 7 parts of tributyl citrate, 5 parts of a calcium-zinc composite heat stabilizer, 1 part of a polyethylene wax, 4 parts of the compatibilizer prepared above, and 15 parts of the rare earth antibacterial agent prepared above are accurately weighed by weight and set aside; S2 raw material premixing: add the weighed dry PVC carrier resin and part of the titanate coupling agent into a mixing device with heating and vacuuming functions, fully mix the dispersant and the PVC resin at a low temperature of 70°C and a stirring speed of 450r / min for 20 minutes, then gradually increase the temperature to 110°C, turn on the vacuuming device at the same time, control the pressure in the system at -0.07MPa, slowly add the rare earth antibacterial agent obtained by pretreatment, continue stirring for 25 minutes during the addition process, and keep the stirring speed at 550r / min. Use negative pressure to remove air and moisture in the system to avoid oxidation and agglomeration of the antibacterial agent; S3 coupling treatment: the material treated above was transferred to a reactor, and the material was first wetted at 90°C for 13 minutes by a stepwise heating method, and then heated to 120°C, and the remaining titanate coupling agent was slowly added, and the reaction was carried out for 25 minutes under a stirring speed of 800 r / min; S4 Mixing and plasticizing: Add the coupled material, tributyl citrate, calcium zinc composite heat stabilizer, polyethylene wax and a compatibilizer prepared by mixing according to a certain proportion into the hopper of a twin-screw extruder. The temperature of the first zone of the twin-screw extruder is 155°C, the temperature of the second zone is 170°C, the temperature of the third zone is 180°C, the temperature of the fourth zone is 185°C, the temperature of the die head is 190°C, and the screw speed is controlled at 200r / min; at the same time, supercritical carbon dioxide with a pressure of 10MPa is injected at 2% of the mass of the material, and the injection is continued and reacted for 15 minutes to evenly disperse additives such as rare earth antibacterial agents in the PVC matrix, reduce the melt viscosity and form a microporous structure; S5 melt extrusion: adopt high shear mixing section, set vacuum exhaust port in the middle of extruder, accurately control vacuum degree at 0.085MPa, remove volatile water and coupling agent by-products, control die pressure at 12MPa, and extrude material into strips through die; S6 granulation molding: water-cooled strand pelletizing is adopted, and the extruded strips are cooled through a water trough, and the water temperature is controlled at 25°C, so that the material can be quickly cooled and solidified within 2 minutes; the cooled material is pelletized by a pelletizer, and the speed of the pelletizer is controlled at 250r / min. The diameter after cutting is 2.5mm, and it is dried in a 60°C oven for 4 hours. At the same time, unqualified particles and scraps are collected, crushed and screened, and then re-added to the raw materials at a mass ratio of 8% for recycling, to obtain rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condenser water pipes.

[0046] Example 2

[0047] S1. Raw material pretreatment: weigh 3 parts by weight of an inorganic oxide mixture of zinc oxide, 2 parts by weight of manganese oxide, 1 part by weight of titanium oxide, and 5 parts by weight of a rare earth oxide mixture of nano-lanthanum-cerium composite oxide, 2 parts by weight of praseodymium oxide, and 1 part by weight of neodymium oxide, and mix them in a ratio of 3:7 between the mass ratio of rare earth and inorganic oxide, and prepare a rare earth antibacterial agent by a doping process, through mixing, mechanical dispersion, high-energy dispersion, secondary mechanical dispersion, drying, tunnel kiln firing, and grinding; weigh 4 parts by weight of a maleic anhydride grafted PVC compatibilizer and 2 parts by weight of dioctyl terephthalate or epoxidized soybean oil, and mix the weighed The two raw materials are added into a high-speed mixer or a stirrer, and mixed to prepare a composite of a maleic anhydride grafted PVC compatibilizer and dioctyl terephthalate or epoxy soybean oil, at a mixing speed of 500 r / min and a mixing time of 10 minutes, to obtain a compatibilizer; the PVC carrier resin is dried at 80° C. for 2 hours to remove moisture, and 80 parts of the dried PVC carrier resin, 0.5 parts of a titanate coupling agent, 5 parts of tributyl citrate, 4 parts of a calcium-zinc composite heat stabilizer, 0.5 parts of a polyethylene wax, 3 parts of the compatibilizer prepared above, and 10 parts of the rare earth antibacterial agent prepared above are accurately weighed by weight and set aside; S2 raw material premixing: add the weighed dry PVC carrier resin and part of the titanate coupling agent into a mixing device with heating and vacuuming functions, fully mix the dispersant and the PVC resin at a low temperature of 60°C and a stirring speed of 300r / min for 15 minutes, gradually increase the temperature to 100°C, turn on the vacuum device at the same time, control the pressure in the system at -0.06MPa, slowly add the rare earth antibacterial agent obtained by pretreatment, continue stirring for 20 minutes during the addition process, and keep the stirring speed at 400r / min. Use negative pressure to remove air and moisture in the system to avoid oxidation and agglomeration of the antibacterial agent; S3 coupling treatment: the material treated above was transferred to a reactor, and the material was first wetted at 80°C for 10 minutes by a stepwise heating method, and then heated to 110°C, and the remaining titanate coupling agent was slowly added, and the reaction was carried out for 20 minutes under the condition of a stirring speed of 600 r / min; S4 Mixing and plasticizing: Add the coupled material, tributyl citrate, calcium zinc composite heat stabilizer, polyethylene wax and a compatibilizer prepared by mixing according to a certain proportion into the hopper of a twin-screw extruder. The temperature of the first zone of the twin-screw extruder is 160°C, the temperature of the second zone is 175°C, the temperature of the third zone is 185°C, the temperature of the fourth zone is 190°C, the temperature of the die head is 195°C, and the screw speed is controlled at 1250r / min; at the same time, supercritical carbon dioxide with a pressure of 12MPa is injected at 3% of the mass of the material, and the injection is continued and reacted for 20 minutes to evenly disperse additives such as rare earth antibacterial agents in the PVC matrix, reduce the melt viscosity and form a microporous structure; S5 melt extrusion: adopt high shear mixing section, set vacuum exhaust port in the middle of extruder, accurately control vacuum degree at 0.09MPa, remove volatile water and coupling agent by-products, control die pressure at 15MPa, and extrude material into strips through die; S6 granulation molding: water-cooled strand pelletizing is adopted, and the extruded strips are cooled through a water trough, and the water temperature is controlled at 30°C, so that the material is quickly cooled and solidified within 3 minutes; the cooled material is pelletized by a pelletizer, and the speed of the pelletizer is controlled at 300r / min. The diameter after cutting is 3mm, and it is dried in an oven at 50-65°C for 5 hours. At the same time, unqualified particles and scraps are collected, crushed and screened, and then re-added to the raw materials at a mass ratio of 10% for recycling, to obtain rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condenser water pipes.

[0048] Example 3

[0049] S1. Raw material pretreatment: Weigh 4 parts by weight of an inorganic oxide mixture of zinc oxide, 5 parts by weight of manganese oxide, 5 parts by weight of titanium oxide, and 7 parts by weight of a rare earth oxide mixture of nano-lanthanum-cerium composite oxide, 4 parts by weight of praseodymium oxide, and 3 parts by weight of neodymium oxide, and mix them in a ratio of 3:7 between the rare earth and inorganic oxides. Use a doping process to prepare a rare earth antibacterial agent through mixing, mechanical dispersion, high-energy dispersion, secondary mechanical dispersion, drying, tunnel kiln firing, and grinding. Weigh 6 parts by weight of a maleic anhydride grafted PVC compatibilizer and 4 parts of dioctyl terephthalate or epoxidized soybean oil. The raw materials are added into a high-speed mixer or a stirrer, and mixed to prepare a composite of a maleic anhydride grafted PVC compatibilizer and dioctyl terephthalate or epoxy soybean oil, the mixing speed is 1500r / min, and the mixing time is 30 minutes to obtain a compatibilizer; the PVC carrier resin is dried at 100°C for 4 hours to remove moisture, and 90 parts of the dried PVC carrier resin, 2.0 parts of a titanate coupling agent, 10 parts of tributyl citrate, 6 parts of a calcium-zinc composite heat stabilizer, 1.5 parts of a polyethylene wax, 5 parts of the compatibilizer prepared above, and 20 parts of the rare earth antibacterial agent prepared above are accurately weighed by weight and set aside; S2 raw material premixing: add the weighed dry PVC carrier resin and part of the titanate coupling agent into a mixing device with heating and vacuuming functions, fully mix the dispersant and the PVC resin at a low temperature of 80°C and a stirring speed of 600r / min for 25 minutes, gradually increase the temperature to 120°C, turn on the vacuuming device at the same time, control the pressure in the system at -0.08MPa, slowly add the rare earth antibacterial agent obtained by pretreatment, continue stirring for 30 minutes during the addition process, and keep the stirring speed at 700r / min. Use negative pressure to remove air and moisture in the system to avoid oxidation and agglomeration of the antibacterial agent; S3 coupling treatment: the material treated above was transferred to a reactor, and the temperature was raised in stages, first at 100°C for 15 minutes, then the temperature was raised to 130°C, and the remaining titanate coupling agent was slowly added, and the reaction was carried out for 30 minutes under the condition of a stirring speed of 1000 r / min; S4 is mixing and plasticizing, S5 is melt extruding, and S6 is granulating and molding. The steps are operated in the same manner as in Example 2 to obtain a rare earth antibacterial masterbatch specially used for PVC antibacterial air-conditioning condensing water pipes.

[0050] Example 4

[0051] S1 raw material pretreatment, S2 raw material premixing, S3 coupling treatment, the steps are the same as in Example 2; S4 mixing and plasticizing: adding the coupled material, tributyl citrate, calcium zinc composite heat stabilizer, polyethylene wax and a compatibilizer prepared by mixing in proportion into the hopper of a twin-screw extruder, the temperature of the first zone of the twin-screw extruder is 150°C, the temperature of the second zone is 165°C, the temperature of the third zone is 175°C, the temperature of the fourth zone is 180°C, the temperature of the die head is 185°C, the screw speed is controlled at 150r / min, and the reaction is carried out for 10 minutes to evenly disperse additives such as rare earth antibacterial agents in the PVC matrix, reduce the melt viscosity and form a microporous structure; S5 melt extrusion: adopt high shear mixing section, set vacuum exhaust port in the middle of extruder, accurately control vacuum degree at 0.08MPa, remove volatile water and coupling agent by-products, control die pressure at 10MPa, and extrude material into strips through die head; S6 granulation molding: water-cooled strand pelletizing is adopted, and the extruded strips are cooled through a water trough, and the water temperature is controlled at 20°C, so that the material can be quickly cooled and solidified within 1 minute; the cooled material is pelletized by a pelletizer, and the speed of the pelletizer is controlled at 200r / min. The diameter after cutting is 2mm, and it is dried in a 50°C oven for 3 hours. At the same time, unqualified particles and scraps are collected, crushed and screened, and then re-added to the raw materials at a mass ratio of 5% for recycling, to obtain rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condenser water pipes.

[0052] Comparative Example 1 S1 raw material pretreatment: weigh 15 parts of common zinc oxide as an antibacterial agent; weigh 5 parts by weight of maleic anhydride grafted PVC compatibilizer and 3 parts of dioctyl terephthalate or epoxidized soybean oil, add the weighed two raw materials into a high-speed mixer or a stirrer, mix and prepare a composite of maleic anhydride grafted PVC compatibilizer and dioctyl terephthalate or epoxidized soybean oil, the mixing speed is 1000r / min, the mixing time is 20 minutes, and the compatibilizer is obtained; dry the PVC carrier resin at 90°C for 3 hours to remove moisture, accurately weigh 85 parts by weight of the dried PVC carrier resin, 1 part of a titanate coupling agent, 7 parts of tributyl citrate, 5 parts of a calcium-zinc composite heat stabilizer, 1 part of a polyethylene wax, 4 parts of the compatibilizer prepared above, and 15 parts of common zinc oxide antibacterial agent, and set them aside; S2 raw material premixing, S3 coupling treatment, S4 mixing and plasticizing, S5 melt extrusion, S6 granulation and molding, the steps are the same as those in Example 1, and PVC antibacterial masterbatch without using rare earth antibacterial agent is obtained.

[0053] Comparative Example 2 S1 raw material pretreatment: 85 parts of PVC carrier resin were dried at 90°C for 3 hours to remove moisture; 1.0 parts of calcium stearate, 7.0 parts of dibutyl phthalate, 5.0 parts of lead salt heat stabilizer, 1.0 parts of paraffin wax and 15 parts of silver ion antibacterial agent were accurately weighed and set aside; S2 raw material mixing: add the dried PVC carrier resin and 1.0 part of calcium stearate into a common mixer, mix at a temperature of 70°C and a stirring speed of 400r / min for 20 minutes; add 15 parts of silver ion antibacterial agent, continue stirring for 20 minutes, and keep the stirring speed at 500r / min; S3 plasticization and extrusion: add the mixed materials into a single screw extruder, the temperature of zone 1 is 150°C, the temperature of zone 2 is 165°C, the temperature of zone 3 is 175°C, the temperature of zone 4 is 180°C, the temperature of the die is 185°C, the screw speed is controlled at 150r / min, react for 10 minutes, and the material is extruded into strips through the die head; S4 granulation molding: water-cooled strand pelletizing is adopted, and the extruded strips are cooled through a water trough, and the water temperature is controlled at 25°C, so that the material is quickly cooled and solidified within 2 minutes; the cooled material is pelletized by a pelletizer, and the speed of the pelletizer is controlled at 250r / min, and the diameter after cutting is 2.5mm; the pelletized particles are dried in a 60°C oven for 4 hours to obtain traditional PVC antibacterial masterbatch.

[0054] 1. Performance Testing The performance tests were conducted on the rare earth antibacterial masterbatch specially used for PVC antibacterial air-conditioning condenser water pipes prepared in Examples 1-4 and the PVC antibacterial masterbatch prepared in Comparative Examples 1-2.

[0055] 1.1 Antibacterial performance test The standard antibacterial test method GB / T21510-2008 "Nano-inorganic material antibacterial property detection method" was adopted, and Escherichia coli and Staphylococcus aureus were selected as test strains. Under a sterile environment, a certain amount of test strains were evenly inoculated on a nutrient agar medium plate. After being evenly distributed, a round filter paper with a diameter of 6 mm that had been sterilized at high temperature was dipped with sterile tweezers into the extract of the PVC antibacterial masterbatch prepared in Example 1-4 and Comparative Example 1-2 (the antibacterial masterbatch was mixed and shaken with a specific solvent in a certain proportion according to the prescribed extraction conditions to obtain the extract), and then the filter paper was attached to the culture medium plate inoculated with the strains, and 3 parallel samples were set for each sample. After the plate was placed in a 37°C constant temperature incubator for 24 hours, the formation of the antibacterial zone around the filter paper was observed, the diameter of the antibacterial zone was measured and the data was recorded. The larger the diameter of the antibacterial zone, the stronger the antibacterial property of the antibacterial masterbatch. At the same time, the antibacterial rate is calculated, antibacterial rate = (initial bacterial count - bacterial count after contact with antibacterial material) / initial bacterial count × 100%, in order to more accurately evaluate the antibacterial performance.

[0056] Table 1 Antibacterial rate of each PVC antibacterial masterbatch prepared in the examples and comparative examples against Escherichia coli and Staphylococcus aureus

[0057] Result analysis: The antibacterial rates of the rare earth antibacterial masterbatches for PVC antibacterial air conditioner condenser pipes prepared in Examples 1-4 are all above 94%, showing excellent antibacterial properties. Among them, Example 1 has the highest antibacterial rate against Escherichia coli, reaching 98%, and the antibacterial rate against Staphylococcus aureus is also as high as 97%, which shows that the PVC antibacterial masterbatch of the present invention has high antibacterial ability and can effectively inhibit the growth of Escherichia coli and Staphylococcus aureus. The PVC antibacterial masterbatch prepared in Comparative Example 1 uses ordinary zinc oxide as an antibacterial agent, and the antibacterial rate is significantly lower than that of the embodiment. The antibacterial rates of Escherichia coli and Staphylococcus aureus are 85% and 83%, respectively, indicating that the antibacterial performance of ordinary zinc oxide is relatively weak. The PVC antibacterial masterbatch prepared in Comparative Example 2 uses a silver ion antibacterial agent, and the antibacterial rates are lower, 80% and 78%, respectively. Although the silver ion antibacterial agent has certain antibacterial properties, it is not as effective as the rare earth antibacterial masterbatch of the present invention in this application scenario.

[0058] The results show that the antibacterial performance of the PVC antibacterial masterbatch containing rare earth antibacterial agent is significantly better than that of the product of comparative example 1 without using rare earth antibacterial agent and comparative example 2 using traditional silver ion antibacterial agent. Among them, the unique electronic structure of the rare earth element in the PVC antibacterial masterbatch of the present invention makes it have antibacterial activity, and the nano-lanthanum-cerium composite oxide and the like synergistically act with zinc oxide to enhance the antibacterial effect, while the antibacterial performance of ordinary zinc oxide is limited, and the silver ion antibacterial agent does not give full play to its advantages in this system. Therefore, the PVC antibacterial masterbatch of the present invention significantly improves the antibacterial performance through the synergistic effect of the rare earth antibacterial agent, which is better than the traditional antibacterial agent.

[0059] 1.2 Thermal stability test Thermogravimetric analysis (TGA) test was performed using a thermogravimetric analyzer. 5-10 mg of the PVC antibacterial masterbatch samples prepared in Examples 1-4 and Comparative Examples 1-2 were taken respectively and placed in an alumina crucible. At a heating rate of 10°C / min, the temperature was raised from room temperature to 600°C in a nitrogen atmosphere with a flow rate of 50 mL / min. The mass change of the sample at different temperatures was recorded to determine the initial decomposition temperature of the sample (the temperature corresponding to 5% weight loss). The higher the initial decomposition temperature, the better the thermal stability, so as to evaluate the effect of rare earth antibacterial agents and other additives on the thermal stability of PVC antibacterial masterbatch.

[0060] Table 2 Quality retention rate of each PVC antibacterial masterbatch prepared in the examples and comparative examples at different temperatures

[0061] Result analysis: The mass retention rate of the rare earth antibacterial masterbatch for PVC antibacterial air conditioner condenser water pipe prepared in Examples 1-4 was above 95% at 200°C, showing good thermal stability. As the temperature increased, the mass retention rate gradually decreased, but it still retained about 30% at 500°C, indicating that the PVC antibacterial masterbatch of the present invention can still maintain a certain stability at high temperatures. The PVC antibacterial masterbatch prepared in Comparative Example 1 used ordinary zinc oxide as an antibacterial agent, and its thermal stability was slightly poor, with a mass retention rate of 92% at 200°C and only 15% at 500°C. The PVC antibacterial masterbatch prepared in Comparative Example 2 used a traditional formula (containing lead salt heat stabilizer, etc.), and had the worst thermal stability, with a mass retention rate of only 90% at 200°C and only 10% at 500°C, indicating that the traditional formula is easily decomposed at high temperatures and has insufficient thermal stability.

[0062] It is generally shown that at the same temperature, the mass retention rate of Examples 1-4 is higher than that of Comparative Examples 1-2, and the initial decomposition temperature of the Examples is higher, indicating that the synergistic effect of rare earth antibacterial agents and other additives such as calcium zinc composite heat stabilizers improves the thermal stability of PVC antibacterial masterbatch. Among them, the rare earth compound in the PVC antibacterial masterbatch of the present invention can combine with the hydrogen chloride produced by the degradation of PVC to inhibit its autocatalytic degradation, and the calcium zinc composite heat stabilizer can also effectively delay the thermal decomposition of PVC, thereby jointly improving the thermal stability of the product. Therefore, the PVC antibacterial masterbatch of the present invention significantly improves the thermal stability by using an optimized formula such as a calcium zinc composite heat stabilizer, and is more suitable for high-temperature processing and use environments.

[0063] 1.3 Mechanical properties test The tensile strength and elongation at break tests were conducted in accordance with GB / T1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics". The PVC antibacterial masterbatch prepared in Examples 1-4 and Comparative Examples 1-2 was injection molded into standard dumbbell-shaped specimens using an injection molding machine, and 5 specimens were prepared for each group of samples. The test was conducted using a universal material testing machine under the environmental conditions of room temperature (23±2)°C and relative humidity (50±5)%. The tensile speed was set to 50mm / min, and a tensile force was applied to the specimen, and the maximum tensile force at break and the gauge length elongation at break were recorded. The tensile strength calculation formula is: tensile strength = maximum tensile force / initial cross-sectional area of ​​the specimen; the elongation at break calculation formula is: elongation at break = (gauge length at break - initial gauge length) / initial gauge length × 100%. The average values ​​of the tensile strength and elongation at break of each group of specimens were calculated, and the differences between different samples were compared to evaluate the effects of rare earth antibacterial agents and other ingredients on the mechanical properties of PVC antibacterial masterbatch.

[0064] Table 3 Tensile strength and elongation at break of each PVC antibacterial masterbatch prepared in the examples and comparative examples

[0065] Result analysis: The tensile strength of the rare earth antibacterial masterbatch for PVC antibacterial air conditioner condenser pipe prepared in Examples 1-4 is between 33-36 MPa, and the elongation at break is between 390-420%, indicating that the PVC antibacterial masterbatch of the present invention has good mechanical properties, with both high strength and good flexibility. The tensile strength of the PVC antibacterial masterbatch prepared in Comparative Example 1 is 30 MPa, the elongation at break is 350%, and the mechanical properties are slightly worse. The tensile strength of the PVC antibacterial masterbatch prepared in Comparative Example 2 is 28 MPa, the elongation at break is 320%, and the mechanical properties are the worst. This is because the plasticizer and heat stabilizer used in the traditional formula have insufficient toughening and strengthening effects on the material.

[0066] Comprehensive description of the reasonable formula of rare earth antibacterial agents and related additives in the embodiments of the present invention helps to enhance the mechanical properties of PVC antibacterial masterbatch. Among them, the titanate coupling agent in the PVC antibacterial masterbatch of the present invention improves the interface bonding between the inorganic filler and the PVC matrix, and the plasticizers such as tributyl citrate increase the flexibility of the molecular chain, and jointly improve the tensile strength and elongation at break of the material. Therefore, the PVC antibacterial masterbatch of the present invention uses an optimized formula such as environmentally friendly plasticizer tributyl citrate, while maintaining the antibacterial properties, significantly improving the mechanical properties, making it more suitable for application scenarios such as air conditioning condensation water pipes that require certain strength and flexibility.

[0067] 1.4 Environmental performance test Inductively coupled plasma mass spectrometry (ICP-MS) was used to determine the heavy metal content of lead, cadmium, mercury and chromium in the PVC antibacterial masterbatch prepared in Examples 1-4 and Comparative Examples 1-2. An appropriate amount of sample was weighed, and after digestion treatment, the digestion solution was injected into the ICP-MS instrument, and the content of each heavy metal element in the sample was calculated according to the standard curve, and compared with the relevant environmental protection standards to determine whether the heavy metal content of the sample meets the environmental protection requirements.

[0068] Table 4 Contents of heavy metals such as lead, cadmium, mercury, and chromium in each PVC antibacterial masterbatch prepared in the examples and comparative examples

[0069] Result analysis: The contents of heavy metals such as lead, cadmium, mercury, and chromium in the rare earth antibacterial masterbatch for PVC antibacterial air conditioner condenser pipes prepared in Examples 1-4 are far lower than the limits of relevant environmental protection standards (usually lead <100 mg / kg, cadmium <100 mg / kg, mercury <10 mg / kg, chromium <1000 mg / kg), indicating that the PVC antibacterial masterbatch of the present invention has good environmental performance. The heavy metal content of the PVC antibacterial masterbatch prepared in Comparative Example 1 is slightly higher, but it still meets environmental protection requirements, which is due to the use of a small amount of non-environmentally friendly raw materials. The heavy metal content of the PVC antibacterial masterbatch prepared in Comparative Example 2 is relatively high, especially the lead content reaches 1.0 mg / kg and the chromium content reaches 0.6 mg / kg, which far exceeds the limits of environmental protection standards, indicating that the lead salt heat stabilizer used in the traditional formula contains a large amount of heavy metals, which is potentially harmful to the environment and human health.

[0070] The results show that the raw materials and preparation process used in the PVC antibacterial masterbatch of the present invention effectively control the introduction of heavy metal content, and the use of rare earth antibacterial agents reduces the risk of heavy metal pollution while ensuring performance. Therefore, the PVC antibacterial masterbatch of the present invention fully meets environmental protection requirements by using environmentally friendly raw materials such as calcium-zinc composite heat stabilizers, avoids the problem of excessive heavy metals in traditional PVC materials, and has good environmental friendliness.

[0071] In summary, the rare earth antibacterial masterbatch for PVC antibacterial air conditioner condenser pipe prepared in Examples 1-4 has certain advantages in antibacterial performance, thermal stability, mechanical properties and environmental performance compared with Comparative Examples 1-2. The PVC antibacterial masterbatch of the present invention exhibits excellent antibacterial performance, and the antibacterial rate against Escherichia coli and Staphylococcus aureus is significantly better than that of traditional antibacterial agents such as ordinary zinc oxide and silver ion antibacterial agents; by optimizing the formula, the PVC antibacterial masterbatch of the present invention can still maintain a high quality retention rate at high temperature, and the thermal stability is significantly better than the traditional formula; while maintaining the antibacterial performance, the PVC antibacterial masterbatch of the present invention significantly improves the mechanical properties by using environmentally friendly plasticizers and other optimized formulas, and has both high strength and good flexibility; at the same time, the PVC antibacterial masterbatch of the present invention fully meets environmental protection requirements, and the heavy metal content is far lower than the relevant standard limit, avoiding the problem of excessive heavy metals in traditional PVC materials.

[0072] 2. Application Verification The PVC antibacterial masterbatch prepared in Example 1 was used in the production of air conditioning condensation water pipes, and its antibacterial performance, odor and other related performance indicators were evaluated through long-term actual use tests. The air conditioning condensation water pipe produced by the PVC antibacterial masterbatch prepared in Example 1 was installed in an actual air conditioning system to ensure that it worked under normal operating conditions, and the pipes were tested 1 month, 2 months, 3 months and 6 months after operation.

[0073] 2.1 Plaque growth Using the microbial swab method, multiple points are randomly selected from the inner wall of the pipeline for surface swab sampling. The swab samples are inoculated on nutrient agar medium and placed in a 37°C constant temperature incubator for 48 hours. The colony formation on the culture medium is observed and the total colony count is calculated. If the total colony count is less than 100 CFU / cm² within 1 month and the total colony count does not increase by more than 10 times within 6 months, the antibacterial performance is considered good; if the total colony count exceeds 1000 CFU / cm² within 6 months, the antibacterial performance is considered poor.

[0074] 2.2 Odor Use a professional olfactory detector (such as an electronic nose) to detect the odor of the condensed water discharged from the pipe, or have a professional olfactory inspector manually smell the condensed water discharged from the pipe and record the odor intensity. If the odor intensity is lower than level 1 (no obvious odor) within 1 month and does not exceed level 2 (slight odor but not uncomfortable) within 6 months, the odor is considered to be well controlled; if the odor intensity exceeds level 3 (obvious odor and uncomfortable) within 6 months, the odor is considered to be poorly controlled.

[0075] 2.3 Pipeline inner wall corrosion Use an ultrasonic thickness gauge to measure the thickness change of the inner wall of the pipeline and record the wall thickness data at different time points. If the thickness of the inner wall of the pipeline decreases by no more than 0.1mm within 6 months, the pipeline is considered to have good corrosion resistance.

[0076] 2.4 Condensate water quality Collect condensate samples regularly to test its pH value, turbidity, total colony count and other indicators. The pH value should be maintained between 6.5-8.5, the turbidity should not exceed 10NTU, and the total colony count should not exceed 100CFU / mL; if the condensate water quality continues to meet the above standards within 6 months, the water quality is considered good.

[0077] Table 5 Performance changes of PVC antibacterial masterbatch prepared in Example 1 at different time points when actually used in air conditioning condensation water pipes

[0078] Result analysis: The total colony count of the air-conditioning condensing water pipe prepared by the PVC antibacterial masterbatch of the present invention increased from 50 CFU / cm² to 120 CFU / cm² within 6 months, and the growth was relatively slow; the total colony count at 6 months was 120 CFU / cm², which was far below the standard of 1000 CFU / cm², indicating that the antibacterial performance was sustained and effective, and the antibacterial effect was good; it showed that the PVC antibacterial masterbatch of the present invention could effectively inhibit the growth of bacteria and maintain the sanitary state of the air-conditioning condensing water pipe in practical applications. The odor intensity of the air-conditioning condensing water pipe prepared by the PVC antibacterial masterbatch of the present invention increased from level 0.5 to level 1.2 within 6 months, and was always in the range of slight odor and no discomfort (no more than level 2); it showed that the PVC antibacterial masterbatch of the present invention could effectively reduce the generation of odor, maintain the freshness of indoor air, and meet the high requirements of modern buildings for indoor air quality. The air-conditioning condensate pipe prepared by the PVC antibacterial masterbatch of the present invention has a reduced inner wall thickness of 0.05 mm within 6 months, which is far below the standard of 0.1 mm, indicating that the corrosion resistance of the pipe is good; it shows that the PVC antibacterial masterbatch of the present invention can effectively prevent pipe corrosion, extend the service life of the pipe, and reduce maintenance costs. The pH value of the condensed water of the air-conditioning condensate pipe prepared by the PVC antibacterial masterbatch of the present invention is between 6.5-8.5, which meets the standard, indicating that the pH value of the condensed water is stable; the turbidity does not exceed 10 NTU within 6 months, which meets the standard, indicating that the clarity of the condensed water is good; the total colony count does not exceed 100 CFU / mL within 6 months, which meets the standard, indicating that the microbial content of the condensed water is low and the water quality is good; the pH value, turbidity and total colony count of the condensed water all meet the standard, indicating that the PVC antibacterial masterbatch of the present invention can ensure the good water quality of the condensed water and ensure the normal operation of the air-conditioning system.

[0079] In summary, the PVC antibacterial masterbatch of the present invention exhibits excellent antibacterial properties, odor control ability, corrosion resistance and condensate water quality control ability in practical applications, can effectively solve the problems existing in traditional PVC condensate pipes, and meet the high requirements of modern society for indoor air quality and the hygiene and durability of building facilities.

[0080] 3. High temperature durability test The PVC antibacterial air conditioning condenser pipe special rare earth antibacterial masterbatch prepared in Example 1-4 and the PVC antibacterial masterbatch prepared in Comparative Example 1-2 were used to produce standard-sized air conditioning condenser pipes. The pipes were placed in 95°C hot water to ensure that the pipes were completely immersed. The immersion time was 7 days, during which the water temperature was kept constant. The antibacterial performance of the soaked pipes was tested under high temperature conditions using the JC / T939-2004 "Antibacterial Performance of Antibacterial Plastic Pipes for Construction" standard. The test strains included Escherichia coli and Staphylococcus aureus. Escherichia coli and Staphylococcus aureus were cultured to the logarithmic growth phase and prepared into a concentration of 1×10 6 CFU / mL of bacterial solution; rinse the soaked pipe surface with sterile saline for 3 times to remove impurities attached to the surface; evenly spread the bacterial solution on the pipe surface, with an inoculation volume of 1mL / cm² for each bacterial solution, place the treated pipe in a sterile culture dish, and culture it in a 37℃ constant temperature incubator for 48 hours; after the culture is completed, rinse the pipe surface with sterile saline, and spread the rinse solution on the nutrient agar medium after gradient dilution, and count the colonies after culture at 37℃ for 24 hours; calculation of antibacterial rate: antibacterial rate = (number of colonies in the control group - number of colonies in the experimental group) / number of colonies in the control group × 100%.

[0081] Table 6 Changes in the antibacterial properties of each PVC antibacterial masterbatch prepared in the examples and comparative examples under high temperature conditions

[0082] Results analysis: In the high temperature durability test, the PVC antibacterial masterbatch prepared in Examples 1-4 showed significantly better antibacterial performance durability than that of Comparative Examples 1-2. After being soaked in hot water at 95°C for 7 days, the antibacterial rate of Escherichia coli in Examples 1-4 only decreased by 1-3 percentage points (Example 1 decreased by 2%, Example 2 decreased by 1%, Example 3 decreased by 3%, and Example 4 decreased by 2%), and the antibacterial rate of Staphylococcus aureus also decreased by 1-3 percentage points (Example 1 decreased by 2%, Example 2 decreased by 1%, Example 3 decreased by 3%, and Example 4 decreased by 2%). The rare earth antibacterial masterbatch specially used for PVC antibacterial air conditioning condenser water pipes prepared in Examples 1-4 showed good antibacterial durability under high temperature conditions, and the special structure and chemical stability of the rare earth antibacterial agent enabled it to maintain a high antibacterial activity under high temperature environment.

[0083] In contrast, Comparative Example 1 used ordinary zinc oxide as an antibacterial agent. After immersion, the antibacterial rate of Escherichia coli decreased by 5 percentage points, and the antibacterial rate of Staphylococcus aureus decreased by 5 percentage points; Comparative Example 2 used silver ion antibacterial agents. After immersion, the antibacterial rate of Escherichia coli decreased by 10 percentage points, and the antibacterial rate of Staphylococcus aureus decreased by 11 percentage points; the ordinary zinc oxide and silver ion antibacterial agents used in Comparative Examples 1 and 2 had significantly reduced antibacterial properties under high temperature conditions, indicating that these traditional antibacterial agents are insufficiently stable in high temperature environments and are difficult to meet the needs of long-term high temperature use.

[0084] The high-temperature durability test verifies the durability of the antibacterial performance of the rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condenser water pipes under high temperature conditions. The comprehensive results show that the rare earth antibacterial masterbatch of the present invention can still maintain high-efficiency antibacterial performance under high temperature conditions, while traditional antibacterial agents (ordinary zinc oxide and silver ion antibacterial agents) have poor stability under high temperature environments and are difficult to meet the needs of long-term high-temperature use.

[0085] Therefore, the present invention provides a rare earth antibacterial masterbatch specially used for PVC antibacterial air-conditioning condensation water pipe and its preparation method, which solves the problem that traditional PVC condensation water pipe is easy to breed bacteria and mold, and utilizes the unique antibacterial property and good stability of rare earth antibacterial agent to modify PVC material, so that the obtained condensation water pipe has high antibacterial ability, thereby reducing odor generation, preventing pipeline corrosion, and extending pipeline service life. At the same time, it meets the high requirements of modern society for indoor air quality and building facility hygiene and durability, improves the performance of current PVC air-conditioning condensation water pipe special rare earth antibacterial masterbatch, and promotes the innovation and development of air-conditioning condensation water pipe material technology.

Claims

1. A rare earth antibacterial masterbatch specially used for PVC antibacterial air conditioning condensing water pipe, characterized in that: The invention comprises the following raw materials in parts by weight: 80-90 parts of PVC carrier resin, 10-20 parts of rare earth antibacterial agent, 0.5-2.0 parts of dispersant, 5-10 parts of plasticizer, 4-6 parts of heat stabilizer, 0.5-1.5 parts of lubricant and 3-5 parts of compatibilizer.

2. The rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condensate pipe according to claim 1, characterized in that: The rare earth antibacterial agent comprises inorganic oxides and rare earth oxides, wherein the mass ratio of the inorganic oxides to the rare earth oxides is 18-33:8-14; the inorganic oxides comprise zinc oxide, manganese oxide, and titanium oxide, and the rare earth oxides comprise nano lanthanum-cerium composite oxide, praseodymium oxide, and neodymium oxide.

3. The rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condensate water pipe according to claim 2, characterized in that: The mass ratio of rare earth to inorganic oxide in the inorganic oxide and rare earth oxide is 3:7, the mass ratio of zinc oxide, manganese oxide and titanium oxide is 3-4:2-5:1-5, and the mass ratio of nano lanthanum-cerium composite oxide, praseodymium oxide and neodymium oxide is 5-7:2-4:1-3; the particle size range of the nano lanthanum-cerium composite oxide is 20-80 nanometers, and the molar ratio of lanthanum to cerium is 1:1-5.

4. The rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condensate water pipe according to claim 1, characterized in that: The dispersant is a titanate coupling agent, the plasticizer is an environmentally friendly plasticizer tributyl citrate, the heat stabilizer is a calcium-zinc composite heat stabilizer, and the lubricant is polyethylene wax.

5. The rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condensate water pipe according to claim 1, characterized in that: The compatibilizer is a composite of a maleic anhydride grafted PVC compatibilizer and dioctyl terephthalate or epoxidized soybean oil, and the mass ratio of the maleic anhydride grafted PVC compatibilizer to dioctyl terephthalate or epoxidized soybean oil is 4-6:2-4.

6. A method for preparing rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condensing water pipe, characterized in that: The specific steps include: S1. Raw material pretreatment: a rare earth oxide mixture and an inorganic oxide mixture are mixed in proportion to prepare a rare earth antibacterial agent; a maleic anhydride grafted PVC compatibilizer and dioctyl terephthalate or epoxidized soybean oil are mixed to prepare a compatibilizer; 80-90 parts of PVC carrier resin, 0.5-2.0 parts of titanate coupling agent, 5-10 parts of tributyl citrate, 4-6 parts of calcium zinc composite heat stabilizer, 0.5-1.5 parts of polyethylene wax, 3-5 parts of compatibilizer and 10-20 parts of rare earth antibacterial agent are weighed and set aside; S2 raw material premixing: PVC carrier resin and part of titanate coupling agent are mixed and added with rare earth antibacterial agent; S3 coupling treatment; S4 Mixing and plasticizing: Mix the material with tributyl citrate, calcium zinc composite heat stabilizer, polyethylene wax and compatibilizer, and inject supercritical carbon dioxide; S5 melt extrusion; S6 granulation molding: water-cooled strand cutting to obtain rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condenser water pipe.

7. The method for preparing a rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condensate water pipe according to claim 6, characterized in that: The step S1 raw material pretreatment specifically includes the following operations: S11 Preparation of rare earth antibacterial agent: weigh 3-4 parts of zinc oxide, 2-5 parts of manganese oxide, and 1-5 parts of titanium oxide, and weigh 5-7 parts of nano lanthanum-cerium composite oxide, 2-4 parts of praseodymium oxide, and 1-3 parts of neodymium oxide to mix them so that the mass ratio of the rare earth oxide mixture to the inorganic oxide mixture is 3:7, and perform mechanical dispersion, high-energy dispersion, secondary mechanical dispersion, drying, tunnel kiln firing, and grinding to obtain a rare earth antibacterial agent; Preparation of S12 compatibilizer: Weigh 4-6 parts of maleic anhydride grafted PVC compatibilizer and 2-4 parts of dioctyl terephthalate or epoxidized soybean oil, and mix to obtain a compatibilizer; S13 Preparation of other raw materials.

8. The method for preparing a rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condensate water pipe according to claim 6 or 7, characterized in that: The ethanol solution of the rare earth oxide mixture and the inorganic oxide mixture powder are mechanically dispersed and mixed uniformly to form a paste mixture; high-energy dispersion further refines the particles to form a solid-liquid separation suspension; after the secondary mechanical dispersion restores the uniformity, the obtained paste mixture is thoroughly dried and then fired in a tunnel kiln, and the roasting temperature and time are controlled by a fully automatic intelligent arrangement device. The roasting buffer area is raised from room temperature to 1400-1600°C, the high-temperature roasting zone is 1400-1600°C for 2-4 hours, and the cooling zone takes 1-3 hours; the high-temperature mixed doped oxides that have been roasted are ground, first crushed and initially ground, and then finely ground to a particle size range of 200nm-150000nm to obtain a rare earth antibacterial agent.

9. The method for preparing the rare earth antibacterial masterbatch for PVC antibacterial air-conditioning condensate water pipe according to claim 6, characterized in that: The step S4 of mixing and plasticizing specifically includes the following operations: S41 material addition: adding the coupled material, tributyl citrate, calcium zinc composite heat stabilizer, polyethylene wax and a compatibilizer prepared by mixing according to a certain proportion into the hopper of a twin-screw extruder; S42 temperature setting: The temperature of the first zone of the twin-screw extruder is 150-160℃, the temperature of the second zone is 165-175℃, the temperature of the third zone is 175-185℃, the temperature of the fourth zone is 180-190℃, the temperature of the die head is 185-195℃, and the screw speed is controlled at 150-250r / min; S43 Supercritical carbon dioxide injection: Inject supercritical carbon dioxide at a pressure of 8-12MPa at 1-3% of the material mass, and continue to inject and react for 10-20 minutes.

Citation Information

Patent Citations

  • Inorganic nano antibacterial hard PVC (polyvinyl chloride) and preparation method thereof

    CN110746716A

  • Anti-fog and mildew-proof rare earth antibacterial preservative film and preparation method thereof

    CN118580599A

  • Inorganic nano-antibacterial hard polyvinyl chloride water supply pipe

    CN1493810A

  • Vinyl chloride resin composition and molded article

    JP2019178301A

  • Non-polluting photocatalyst antibacterial masterbatch for non-polluting photocatalyst antibacterial PVC window sash

    KR102583060B1

Cited By

  • Rare earth modified polyvinyl chloride antibacterial composite material as well as preparation method and application thereof

    CN120329670A

  • Rare earth antibacterial auxiliary material and preparation method thereof

    CN121220502A

  • Preparation method of rare earth modified antibacterial polymer master batch

    CN121851423A